2015
DOI: 10.2147/ppa.s75876
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of non-adherence to antiretroviral therapy in adult hospitalized patients, Northwest Ethiopia

Abstract: AimThe aim of this study was to assess the rate of antiretroviral therapy (ART) adherence and to identify any determinants among adult patients.MethodsA cross-sectional study was conducted on 351 ART patients in the ART clinic of the University of Gondar referral hospital. Data were collected by a pretested interviewer-administered structured questionnaire from May to June 2014. Multivariate logistic regression was used to determine factors significantly associated with adherence.ResultsOf 351 study subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
3
28
4
2
Order By: Relevance
“…Similar findings were made in Ethiopia where it was observed that unemployed patients were more likely to be depressed and less likely to socialize, leading to miss appointments and access to health care [23]. Similar findings were also made in Cameron where it was reported that adherence was high among employed patients as compared to unemployed patients [24].…”
Section: Influence Of Economic Factors On Art Adherencesupporting
confidence: 75%
“…Similar findings were made in Ethiopia where it was observed that unemployed patients were more likely to be depressed and less likely to socialize, leading to miss appointments and access to health care [23]. Similar findings were also made in Cameron where it was reported that adherence was high among employed patients as compared to unemployed patients [24].…”
Section: Influence Of Economic Factors On Art Adherencesupporting
confidence: 75%
“…Some of the reasons mentioned in this study, for example forgetfulness, transport problems and work commitments are similar to those reported in other studies [5,8,9]. However, while lack of food was mentioned in this study as reason for missed dose, in Northern Namibia, lack of food was not revealed as a reason for missed doses [9].…”
Section: Respondents' Responses On the Reason/s For Arv Missed Dose (supporting
confidence: 85%
“…Given the large number of patients whose HIV infection will progress to AIDS if adherence is suboptimal, research is urgently needed to determine factors influencing adherence so that the most effective interventions to ensure adherence in African cohorts can be employed [4]. In a study in Ethiopia, 26.5% of the respondents had sub optimal adherence [5]. Locally, a recent study from Northern Namibia reported that 22% of respondents were non-adherent measured by pill count assessment.…”
mentioning
confidence: 99%
“…A study done in North-West Ethiopia showed that the reasons for missing doses were forgetfulness (43.3%) and side-effect of antiretroviral therapy drugs (3%) [27]. Study done in Addis Ababa, Ethiopia showed that the major reasons for non-adherence include simply forgot which was 33.9% [37].…”
Section: Reasons For Non-adherence To Antiretroviral Therapymentioning
confidence: 99%
“…However, study done in North-West Ethiopia found that among reasons for missing doses were forgetfulness 29 (43.3%) and side-effect of antiretroviral therapy drugs 2 (3%) [27].…”
Section: Introductionmentioning
confidence: 98%